2022
DOI: 10.1002/ijgo.14207
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial polyp is associated with a higher prevalence of chronic endometritis in infertile women

Abstract: The prevalence of endometrial polyps (EP) was 32% in a prospective study of 1000 infertile women undergoing hysteroscopic evaluation. 1 EP have been found to have a negative effect on fertility and polypectomy is recommended to obtain an improved pregnancy rate in infertile patients with EP. However, some patients still do not become pregnant after polypectomy. It is essential to elucidate whether other factors affect the implantation environment in infertile patients with EP. Premenopausal women with hysteros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Additional research has also explored the relationship between CE and other factors linked to infertility [19]. A further research observed a greater occurrence of CE among women who are unable to conceive and had endometrial polyps, indicating a possible correlation between these two disorders [20]. Furthermore, studies have examined the diagnostic significance of CD138 for CE, suggesting that CD138 immunohistochemical staining may enhance the rate and precision of CE diagnosis [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional research has also explored the relationship between CE and other factors linked to infertility [19]. A further research observed a greater occurrence of CE among women who are unable to conceive and had endometrial polyps, indicating a possible correlation between these two disorders [20]. Furthermore, studies have examined the diagnostic significance of CD138 for CE, suggesting that CD138 immunohistochemical staining may enhance the rate and precision of CE diagnosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there were no statistically significant correlations found between CE and any other variables. Furthermore, studies have shown a greater occurrence of CE among women who were unable to conceive and have endometrial polyps, suggesting a possible correlation between these two disorders [23,20]. Moreover, the diagnostic significance of CD138 in CE has been investigated, indicating that CD138 immunohistochemical staining has the potential to improve the rate and precision of CE diagnosis [19].…”
Section: Discussionmentioning
confidence: 99%
“…Local inflammation of the endometrium is contributing factor to the formation and recurrence of EPs, while CE involves chronic persistent inflammation of the endometrium that often coexists with EPs [ 9 , 12 , 19 , 21 ]. Our previous retrospective study showed that CE may be a risk factor for EP recurrence in premenopausal women who underwent TCRP [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…These changes can lead to the formation of EPs. Peng et al [ 12 ] found that the occurrences of both solitary polyps and multiple polyps are positively associated with CE.…”
Section: Introductionmentioning
confidence: 99%
“…Whether CD138-positive plasma cells were present in the endometrial tissue samples, as observed on high-power fields (HPF), was counted by an experienced pathologist (YZ). The presence of at least one CD138-positive plasma cell in the endometrial stroma per HPF (400x) was considered indicative of CE, according to previous studies [ 7 , 11 ].…”
Section: Methodsmentioning
confidence: 99%